Miscible chemical ordering in Ti-Cr-Mo quinary system by solid solution of Mo2Ti2AlC3 and Cr2.5Ti1.5AlC3 o-MAXs - Cheng-Feng Du; Chuanchao Wang; Mengfei Xu; Yaqing Xue; Lili Xue; Conghui Meng; Long Wang; Weihong Qi; Xuqing Liu; Hong Yu (Nature Communications)
Abstract Out-of-plane ordering is promising for separately adjusting the heterodesmic chemical bonding inside the MAX phase thus tuning their properties, while constructing the out-of-plane ordered-MAX (o-MAX) is still a challenge. In this work, a strategy towards o-MAX by solid solutions of two existing o-MAXs is verified, i.e., Cr2.5Ti1.5AlC3 and Mo2Ti2AlC3, with controllable stoichiometric ratios (1:2, 1:1, and 2:1). A miscible chemical ordering is observed in three Ti-Cr-Mo quinary MAXs, which inherits the out-of-plane ordering from both parental o-MAXs. Meanwhile, through density functional theory (DFT) calculations, the electronic structure and bonding states inside the quinary o-MAXs are analyzed. Based on the calculations, anisotropic and improved mechanical properties are predicted, which agree with the experimental observed high compressive strength and tunable capacity of energy dissipation. The present work proves a promising way for synthesizing multicomponent o-MAXs.